Mas, Salvador (comp., trad. y estudio preliminar). Alemania y el mundo clásico (1896-1945) (2015)
Mas, Salvador (comp., trad. y estudio preliminar). Alemania y el mundo clásico (1896-1945). Madrid: Plaza y Valdés, 2014. 504 pp.